Direct Distribution of Rents and the Resource Curse in Iran: A Micro-econometric Analysis - Mohammad Reza Farzanegan; Mohammad Habibpour (Center for Economic Studies and ifo Institute (CESifo), 2014)
Our goal is to examine the income inequality and welfare effects of the direct distribution of resource rents and subsequent taxation in Iran. We use rich micro survey data covering more than 36,000 Iranian households in 2009. Our micro-simulations show that the direct distribution of resource rents among all citizens and the imposition of an additional direct income tax have a significant negative effect on the household GINI index and on poverty. We also examine three alternative policies to the resource dividend (RD) policy. The results show that the RD policy is the most successful policy for addressing rents-induced inequality.
Keywords: Q32; Q38; Q43; I30; C15; 330; resource curse; direct rents distribution; poverty; inequality; household survey; Iran